2017
DOI: 10.3892/etm.2017.5239
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of CODA motion analysis system for measuring cervical range of motion in patients with cervical spondylosis and anterior cervical fusion

Abstract: The aim of the present study was to evaluate the reliability of the Cartesian Optoelectronic Dynamic Anthropometer (CODA) motion system in measuring the cervical range of motion (ROM) and verify the construct validity of the CODA motion system. A total of 26 patients with cervical spondylosis and 22 patients with anterior cervical fusion were enrolled and the CODA motion analysis system was used to measure the three-dimensional cervical ROM. Intra- and inter-rater reliability was assessed by interclass correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A variety of neck diseases, such as cervical spondylosis, directly cause limited cervical vertebrae mobility (6). The degree of cervical vertebral ROM reduction is associated with the severity of neck disease (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of neck diseases, such as cervical spondylosis, directly cause limited cervical vertebrae mobility (6). The degree of cervical vertebral ROM reduction is associated with the severity of neck disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical ROM is an indicator of cervical pain and a variety of cervical spine diseases (2). ROM can be used as an evaluation parameter to monitor the effect of cervical disease treatment, including when assessing clinical results after anterior decompression and cervical spine fusion (2,5,6). With ROM measurements, clinicians can adjust treatment plans according to cervical vertebral mobility changes (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a wide variety of methods to evaluate CROM, ranging from more traditional methods (simple visual estimation, inclinometers, or goniometers) ( Youdas, Carey & Garrett, 1991 ; Audette et al, 2010 ) to more recent devices such as smartphone applications ( Tousignant-Laflamme et al, 2013 ; Quek et al, 2014 ; Pourahmadi et al, 2018 ; Stenneberg et al, 2018 ; Rodríguez-Sanz et al, 2018 ) or optoelectronic devices ( Zhongyang et al, 2017 ; Feng et al, 2019 ). A recent systematic review of reliability and validity studies of CROM measurement methods concluded that the CROM device (composed of three inclinometers) was shown to be clinimetrically sound ( Williams et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%